KUALITAS PELAYANAN ADMINISTRASI AKADEMIK PERGURUAN TINGGI SWASTA DI YOGYAKARTA: METODE IMPORTANCE-PERFORMANCE ANALYSIS (IPA) - Shita Lusi Wardhani; Rahmat Purbandono (Jurnal Riset Manajemen dan Bisnis, 2014)
This study aims to measure the quality of service by the Layanan Administrasi Akademik Perguruan Tinggi in Yogyakarta. Quality of service is measured using the concept of SERVQUAL developed by Parasuraman et al. (1985) consists of 10 dimensions. They are tangible, reliability, responsiveness, competence, courtesy, credibility, security, access, communication, understanding the customer. The level of student satisfaction is determined using the formula of Student Satisfaction Index (SSI). Analysis of the difference between expected and perceived the quality of service by the Cartesian diagram using the ImportancePerformance Analysis (IPA) and Wilcoxon Signed Ranks test. This study used a sample of 302 college students in Yogyakarta. The results show that SSI is in a good category. Courstesy and reliability have lowest SSI. Wilcoxon Signed Ranks Test results show that the quality of service received by students is lower than expected for all dimensions. Keywords: Student Satisfaction Index, Importance-Performance Analysis